Justifikasi Hukum Terhadap Pemutusan Hubungan Kerja di Indonesia - Seala Syah Alam; Ryan Saputra Alam (Scientia Integritas Utama, 2022)
The forecast for the global and Indonesian economy which is predicted to be unfavorable in the coming year has raised anticipation in several corporations to lay off workers (PHK), downsizing employees, and employee efficiency. It is necessary to understand the justification attached to the layoffs of employees or workers so that employees, management and the company still adhere to their legal rights and obligations. It was concluded that of the ten reasons for companies to layoffs based on Law no. 13 of 2003, there are 3 (three) reasons, namely reasons related to or attached to the employee or employee's personal, reasons related to employee behavior, and/or reasons related to the running of the company. Each of these reasons must still be based on the stages contained in the reason.